2017
DOI: 10.1093/jnci/djx159
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Serous Endometrial Carcinoma in Women With Pathogenic BRCA1/2 Variant After Risk-Reducing Salpingo-Oophorectomy

Abstract: It has recently been shown that the risk of a rare subtype of endometrial carcinoma (serous type) in women carrying a germline BRCA1/2 pathogenic variant is increased. We assessed the incidence of serous endometrial carcinoma in an independent prospective cohort study of 369 BRCA1/2 women (1779 woman-years of follow-up) who underwent risk-reducing salpingo-oophorectomy by laparoscopy. This occurrence in two BRCA1 carriers led us to estimate that BRCA1/2 carriers present a higher risk than the control populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 13 publications
2
31
1
4
Order By: Relevance
“…Similar results were reported for Australian BRCA1/2 carriers restricted to those who used tamoxifen . Saule et al, in a study of 369 French BRCA1/2 mutation carriers, reported a 3% risk for developing serous endometrial cancer by age 70 years but no increased risk for all endometrial cancer subtypes combined in BRCA1/2 mutation carriers. Recently, an Italian group that analyzed the rate of uterine carcinosarcomas in 1854 high‐risk families reported that 11 families had a case of gynecological carcinosarcoma, including 4 families with a BRCA1 mutation, 4 families with a BRCA2 mutation, and 3 high‐risk families without mutations in either BRCA gene …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar results were reported for Australian BRCA1/2 carriers restricted to those who used tamoxifen . Saule et al, in a study of 369 French BRCA1/2 mutation carriers, reported a 3% risk for developing serous endometrial cancer by age 70 years but no increased risk for all endometrial cancer subtypes combined in BRCA1/2 mutation carriers. Recently, an Italian group that analyzed the rate of uterine carcinosarcomas in 1854 high‐risk families reported that 11 families had a case of gynecological carcinosarcoma, including 4 families with a BRCA1 mutation, 4 families with a BRCA2 mutation, and 3 high‐risk families without mutations in either BRCA gene …”
Section: Discussionsupporting
confidence: 68%
“…Ninety‐five percent confidence intervals (CIs) for the observed‐to‐expected ratio (O:E) for uterine SIRs were calculated assuming a Poisson distribution. To calculate SIRS for serous papillary endometrial cancer, we assumed that the national rates for this cancer type were 10% of the total reported rates for uterine cancer in all age groups, as previously assumed …”
Section: Methodsmentioning
confidence: 99%
“…A distinct phenotype of tumors in a cancer syndrome is considered to be in support of a causal relationship. Although previous studies show contradictory results about excess risk of EC (all histotypes) for gBRCA carriers (6)(7)(8)(9)(10)(11)38), most recent studies did find increased risks to develop serous-like ECs, with reported standardized incidence ratios (SIR) ranging from 14.29 to 32.2 (6,7,10). These SIRs are comparable with the reported relative risk increase for prostate cancer (up to 20-fold) and pancreatic cancer (up to 10fold) for gBRCA2 carriers (1).…”
Section: Discussionmentioning
confidence: 57%
“…Other cancer types reported to be increased in patients with germline BRCA2 mutations (gBRCA) are pancreatic and prostate cancer (3,4). Whether endometrial carcinoma (EC) should be considered part of gBRCA-associated HBOC syndrome is still under debate due to conflicting data (5)(6)(7)(8)(9). A number of studies have shown an increased risk to develop EC especially for gBRCA1 carriers, with highest risks observed for an aggressive subtype of EC-the serous-like ECs (5)(6)(7)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation